Formulasi Sabun Cair Cuci Tangan Antibakteri Ekstrak Etanol Daun Cabe Rawit (Solanum frutescens.L) - Aina fatkhil haque; Elly Mulyani; Jimmy Hendick (Indonesian Journal of Pharmaceutical Education, 2022)
Several studies have shown that cayenne pepper (Solanum frutescens.L) leaf extract has antimicrobial properties In this study, the extraction was carried out by the maceration method. The liquid soap formulation that will be made contains cayenne pepper leaf extract with 0.5%, 1%, 2%. Of all the parameters of the physical properties test carried out. It is known that the ethanol extract of cayenne pepper leaves can be made into liquid soap preparations. Variations in the concentration of ethanol extract of cayenne pepper leaves used in the study showed its effect on organoleptic tests in the form of color and aroma. In the pH test, the pH varied from 9.41-10.65 and the foam height obtained at the 5th minute was 91%, 92%, 93%. For the hedonic test, it was found that the panelists preferred Formula 2 to Formula 1 and Formula 3. Based on the results of the evaluation of the formulation, the best formula is obtained in formula 3.